Implementasi Ergo-Entrepreneurship Secara Partisipatori Mengurangi Kebosanan dan Stres Kerja serta Meningkatkan Sikap Kewirausahaan Pekerja - Sri Arnita, Ni Putu; Lestari Devi, Ni Luh Putu Mia; Sutajaya, I Made (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 9 No 1 (2023): Volume 9 No 1 Tahun 2023, 2023)
Home industry has an important role in Indonesia economy. Home industry of making piranti upakara generally works in groups. The owners of the piranti upakara lay off their workers because existence of health protocols that limit the number of crowds. The piranti upakara workers change professions or become unemployed caused laid-off. The purpose of research is to decrease boredom, work stress, and increase the entrepreneurial attitudes of workers to prove and implement ergo-entrepreneurship with participatory approach. The research by quasi experimental with the treatment by subject design and randomized posttest only group design assessed: (a) implementation of ergo-entrepreneurship with partisipatory approach reducing boredom, was recorded by Boredom Questionnaire; (b) implementation of ergo-entrepreneurship with partisipatory approach decrease work stress recorded by Work Stress Questionnaire; (c) implementation of ergo-entrepreneurship with participatory approach increase the entrepreneurial attitudes, assessed by Entrepreneurial Attitudes Questionnaire. The data were analyzed by paired t-test at a significance level of 5%. The result are: (a) implementation of ergo-entrepreneurship with partisipatory approach, reducing boredom of worker to 40,31% ; (b) reducing work stress of workers to 26,88% ; (c) increase the entrepreneurial attitudes of workers to 45,13% . It concluded that implementation of ergo-entrepreneurship with partisipatory approach reducing boredom, work stress, and improving entrepreneurial attitudes of workers piranti upakara makers.